El Teatro Nacional Cervantes y Teatro Municipal General San Martín durante la última dictadura militar argentina (1976-1983): sistemas de repertorio y prácticas de dirección escénica - Eugenio Schcolnicov (Nuevo mundo - Mundos Nuevos, 2022)
The following paper aims to analyze the theatrical managements developed by Rodolfo Graziano at the Teatro Nacional Cervantes and by Kive Staiff at the Teatro Municipal General San Martín during the last Argentine civil-military dictatorship (1976-1983). We will focus on two axes of analysis: the transformations in the repertory systems of both official institutions during the government of the Military Juntas and the selection criteria of the theater directors who were part of their programming during the same period. The article will elaborate a perspective that shows the contradictory processes of the dynamics of stage production in the state sphere in connection with the cultural policy deployed by the authoritarian regime.